Development of Artificial Intelligence in Building Creativity and Innovation Values of Islamic Education - Faizudin Faizudin; Annisaul Khairat; Irfan Anshori; Ahmad Munji; Wasehudin Wasehudin; Alfurqan Alfurqan; Iskandar Fuaddin (Ta'dib, 2025)
Artificial intelligence has a negative impact on students who lack control in using their gadgets. This study aims to utilize artificial intelligence that affects the world of education especially Islamic education. This research method uses a SWOT analysis developed through a qualitative descriptive approach; the aim is to explain the strengths, weaknesses, opportunities and challenges of artificial intelligence in building the values of creativity and innovation in Islamic education. Data collection techniques use observation, documentation and interviews. Interviews were conducted with 45 students and 9 teachers in the SMP N 1 Pontang environment. The interview technique uses a purposive sampling technique. The results of this study illustrate that artificial intelligence has been applied at SMPN 1 Pontang. The strength aspect of the use of artificial intelligence can improve teachers in terms of their professionalism, can access broader and more varied materials. Weakness aspect; Uncertainty in understanding the context of culture and spirituality. Opportunity aspect; having a lot of access in the digital world to sail to find materials. Challenge aspect; having limitations in understanding the context of Islamic culture, lack of direct touch from teachers, and increasingly limited moral education. The use of artificial intelligence at SMPN 1 Pontang is still relatively early, but its existence has succeeded in attracting students and teachers. Artificial intelligence tools such as grammar, jasper.ai, photomath, beautiful.ai, khan academy are widely used by students to support the educational process towards education that has high creativity and innovation values.┬á